Rehabilitation Center for Teenage Victims of Drug Abuse Based on a Therapeutic Community (TC) in Banten Province with a Behavior Architecture Approach - Rizki Umar Mahardika; Andi Purnomo; Moch Fathoni Setiawan; Ardiyan Adhi Wibowo (Canopy: Journal of Architecture, 2024)
The increasing number of drug abuse cases in Indonesia, particularly among teenagers, indicates that government prevention measures have not been fully effective, as many areas lack adequate rehabilitation centers. These centers are essential for helping victims recover from addiction and reintegrate into society, serving both rehabilitative and preventive functions. Banten Province has several rehabilitation centers, but not all meet the necessary standards. This underscores the need for a specialized Drug Rehabilitation Center focused on teenagers, who are the majority of drug addiction victims. This center will utilize the Therapeutic Community (TC) model, where rehabilitants engage in social rehabilitation activities within their communities, and employ a Behavioral Architecture approach, which responds to users and their environment. The planning and design of this center will involve the analysis of primary and secondary data through five aspects: functional, contextual, technical, performance, and architectural. The Behavioral Architecture approach aims to create spaces that support the physical and mental healing of teenage drug addicts while being responsive to their needs. The analysis results will guide the subsequent design process.